Brain perfusion single-photon emission computed tomography findings in a patient with aicardi syndrome - Aydin, Mustafa; Balci, Tansel Ansal; Kabakus, Nimet (Tubitak Scientific & Technological Research Council Turkey, 2007)
Aicardi syndrome is a rare X-linked dominant genetic disorder characterized by infantile spasms, agenesis or hypogenesis of the corpus callosum, and chorioretinal lacunae. There remain many unresolved questions regarding the clinical features of this disorder. Recent advancements in neuroimaging techniques have allowed us to obtain information about brain development and perfusion. Thus, we present herein the brain single-photon emission computed tomography (SPECT) findings in a 15-month-old female with Aicardi syndrome, which revealed that perfusion had shifted from the posterior to anterior regions. Furthermore, the right temporal lobe was not visualized, while significant hypoperfusion was determined on the occipital regions and left posterior parietal area. SPECT may be a valuable tool for the assessment of the pathologic functional state in patients with Aicardi syndrome.
Keywords: aicardi syndrome; brain scintigraphy; SPECT; mental retardation; neuronal migration disorder; child